Exploring the EFL Students’ Perceptions Towards the Use of Youtube Video Media in Learning English Pronunciation: Positive or Negative? - Mulyani, Mulyani; Chaira, Salwa; Wahyuni, Sri; Rosdiana, Rosdiana; Maulizan, Maulizan; Syahputra, Mulyadi; Aini, Riska Marlisa (Jurnal Ilmiah Teunuleh, 2023)
In this digital era, the use of YouTube video media in education sector becomes a need. Learning by using this media supplies a beneficial effect towards either the teacher or students. Researches related to using media in learning English language from year to year show the steady increase in an attempt to boost the students’ outcomes in English language skills. Yet, there has been found rarely the study exploring the EFL students’ perspectives on using the media in English learning. Therefore, it is critical to establish a study focusing on the EFL students’ perceptions towards the use of media particularly YouTube video media in learning English pronunciation. This study aims at exploring the EFL students’ perceptions towards the use of YouTube video media in learning English pronunciation whether positive or negative. This study employs a qualitative approach using questionnaire and observation sheet to 28 students of SMP 2 Mesjid Raya, Aceh. Therefore, based on the results of the questionnaire, it can be stated that the majority of students responded very positively to the use of YouTube-based video media. This is indicated by the high percentage of all statements on the aspects of students' interest in the use of the media in learning pronunciation. There is a positive significant result shown by the EFL students towards the use of YouTube video media in learning English pronunciation.